2021
DOI: 10.1002/app.51469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non‐metallic fraction of printed circuit boards waste on recycled polyvinyl chloride from waste wires

Abstract: Recycling of electric and electronic equipment is an emerging global issue in order to decrease the high amount of waste deposited on landfill or incinerated, and thus reducing the environmental pollution. Different strategies of eliminating this waste can be applied. In this paper, the non‐metallic fraction of printed circuit boards, due to the contained amount of glass fiber and rigid epoxy matrix, are considered suitable for valorization as reinforcing filler for polyvinyl chloride recovered from the insula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Similarly, the WPCB non-metals have been utilized in polyvinyl chloride (PVC) [111][112][113]. Grigorescu et al demonstrated that a 15-20% non-metallic fraction of WPCB can endow the recycled PVC with properties suitable for reuse as an insulating technical material [114]. Wang et al found that the diameter and contents of glass fiber recovered from WPCB determined the tensile and bending strengths of as-prepared PVC composites [115].…”
Section: Reutilization Of Wpcb Non-metallic Components In Thermoplast...mentioning
confidence: 99%
“…Similarly, the WPCB non-metals have been utilized in polyvinyl chloride (PVC) [111][112][113]. Grigorescu et al demonstrated that a 15-20% non-metallic fraction of WPCB can endow the recycled PVC with properties suitable for reuse as an insulating technical material [114]. Wang et al found that the diameter and contents of glass fiber recovered from WPCB determined the tensile and bending strengths of as-prepared PVC composites [115].…”
Section: Reutilization Of Wpcb Non-metallic Components In Thermoplast...mentioning
confidence: 99%
“…Recycled cable insulation materials are difficult to recycle into insulation due to the technical requirements for these materials. The material can be processed into other technical products, including composites with recycled fillers [ 74 , 75 , 76 ]. Shredded cable insulation is also an additive to cement and bituminous masses [ 77 , 78 , 79 , 80 , 81 , 82 , 83 ].…”
Section: Pvc Recyclingmentioning
confidence: 99%
“…Previous studies by R.M. Grigorescu et al illustrated the incorporation of NMPCB from 0 wt.% to 30 wt.% in recycled PVC (wire grade) using the solvent casting method [23]. Rajesha K Das et al showed that poor mechanical properties were obtained in NM-PCB/recycled PVC (wire grade)-a result of poor compatibility [24].…”
Section: Introductionmentioning
confidence: 99%